2015
DOI: 10.1186/s12887-015-0401-0
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug events in hospitalized children at Ethiopian University Hospital: a prospective observational study

Abstract: BackgroundThe nature and magnitude of adverse drug events (ADEs) among hospitalized children in low-income countries is not well described. The aim of this study was thus, to assess the incidence and nature of ADEs in hospitalized children at a teaching hospital in Ethiopia.MethodsWe used prospective observational method to study children that were hospitalized to Jimma University Specialized Hospital between 1 February and 1 May 2011. ADEs were identified using review of treatment charts, interview of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 41 publications
1
39
2
2
Order By: Relevance
“…A previous local study in the paediatrics ward has shown an incidence of 9.2 adverse drug events per 100 hospital admissions, of which one third could be preventable [6]. As health care managers strive to improve the quality of patient care, there is a growing recognition of the importance of establishing a culture of safety in Ethiopia [7].…”
Section: Introductionmentioning
confidence: 99%
“…A previous local study in the paediatrics ward has shown an incidence of 9.2 adverse drug events per 100 hospital admissions, of which one third could be preventable [6]. As health care managers strive to improve the quality of patient care, there is a growing recognition of the importance of establishing a culture of safety in Ethiopia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Published subsequent to the 2012 systematic review [4], surveys from paediatric settings in sub-Saharan Africa suggested the proportion of admissions due to ADRs to be 5.7% (16/282) in Cape Town, South Africa [19], 4.7% (114/2433) in Eritrea [20], and 0.60% (12/2004) in Lagos, Nigeria [21]. A study from Jimma, Ethiopia, with paediatric adverse drug events as outcome (i.e., a slightly different outcome than ADRs), determined the proportion of admissions to be adverse drug event-related as 0.63% (4/634) [22]. The prevalence of serious ADRs during paediatric admissions was not studied in the 2012 systematic review, although the prevalence of all in-hospital ADRs (i.e., of any seriousness) ranged from 0.6 to 16.8% among included studies [4].…”
Section: Discussionmentioning
confidence: 99%
“…A previous local study61 in paediatrics ward showed an incidence of 9.2 ADEs per 100 admissions, of which one-third were deemed preventable. As healthcare managers strive to improve the quality of patient care, there is a growing recognition of the importance of establishing a culture of patient safety.…”
Section: Introductionmentioning
confidence: 88%